2019
DOI: 10.1002/alr.22423
|View full text |Cite
|
Sign up to set email alerts
|

Manuka honey sinus irrigations in recalcitrant chronic rhinosinusitis: phase 1 randomized, single‐blinded, placebo‐controlled trial

Abstract: Background Manuka honey (MH) has significant antibiofilm activity in vitro and in vivo against Staphylococcus aureus, methicillin‐resistant S aureus (MRSA), and Pseudomonas aeruginosa. This is the first randomized, single‐blinded, placebo‐controlled phase 1 clinical trial investigating the safety and preliminary efficacy of MH with augmented methylglyoxal (MGO) rinses in recalcitrant chronic rhinosinusitis (CRS). Methods Patients were included after previously undergoing endoscopic sinus surgery and presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Clinical studies assessing the efficacy of Manuka honey in treatment resistant post‐surgical patients have not demonstrated superior efficacy over saline alone 1227–1232 . Thamboo et al evaluated 34 AFRS patients, randomized to receive 30 days of atomized MH saline solution to 1 side and saline alone to the contralateral side.…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies assessing the efficacy of Manuka honey in treatment resistant post‐surgical patients have not demonstrated superior efficacy over saline alone 1227–1232 . Thamboo et al evaluated 34 AFRS patients, randomized to receive 30 days of atomized MH saline solution to 1 side and saline alone to the contralateral side.…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…However, during acute exacerbation of their CRS, culture negativity was statistically better in patients who irrigated with MH solution 1230 . A 2019 single‐blinded, placebo‐controlled trial by Ooi et al investigated MH with augmented MGO rinses in recalcitrant CRS patients 1232 . Twenty‐five patients with CRS and positive bacterial culture sinus swab after ESS were randomized to receive 14 days twice daily 16.5% MH + 1.3 mg/mL MGO sinonasal rinses or 10 days of culture‐directed oral antibiotic therapy with concurrent topical or oral placebo.…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…It needed to be above the minimum inhibitory concentration, but below the upper limit of tolerability and the level at which histological epithelial injury occurs, as ascertained by in vitro and unpublished data (N. Sorrel, personal communication, 28 July 2014; E. Leon, personal communication, 16 July 2014) 9,10,20,21 . Only a couple other studies have evaluated manuka honey for nasal use and none in the CF‐CRS population 22‐25 …”
Section: Discussionmentioning
confidence: 99%
“…9,10,20,21 Only a couple other studies have evaluated manuka honey for nasal use and none in the CF-CRS population. [22][23][24][25] This trial does provide data on preliminary effectiveness of manuka honey sinus irrigations in post-ESS subjects with CF-CRS.…”
Section: Secondary Effectiveness Outcome Measuresmentioning
confidence: 99%
“…However, it is difficult to reach a consensus on its use owing to the lack of consistent efficacy data, Lee et al [73] found no significant difference between MH sinus irrigation group and saline sinus irrigation group in patients with CRS. The experimental results reported by Ooi et al [74] revealed that 6 of 10 (60%) patients sinonasal rinses MH demonstrated a reduced bacterial culture rate, with no major adverse events.…”
Section: Manuka Honeymentioning
confidence: 92%